Effects of high-pressure homogenization on phenolics profile, antioxidant activity, α-glucosidase inhibitory activity, and insulin resistance of peach juice during simulated gastrointestinal digestion - Yijin Peng; Shenke Bie; Shengbao Cai; Linyan Zhou; Chaofan Guo (Food Chemistry: X)
This study underscores the potential of high-pressure homogenization (HPH) as a non-thermal processing technique to improve the bioavailability and health benefits of phenolic compounds in peach juice. Following HPH treatment at 300 MPa, the retention of total phenolic and flavonoid content after gastrointestinal digestion increased by 28 % and 20 %, respectively. The bioactivities of peach juice were significantly improved, as evidenced by enhanced antioxidant activity, with DPPH and ABTS free radical scavenging capacities rising by 8.58 % - 26.68 %, and α-glucosidase inhibition improving by 21.40 % - 32.98 %. Furthermore, glucose consumption in insulin-resistant HepG2 cells increased by 17.15 % - 30.00 %. Molecular docking analysis further revealed that key phenolic compounds, including phlorizin and quercetin, interacted effectively with IRS1/PI3K/AKT pathway proteins, contributing to the alleviation of insulin resistance. These findings highlighted HPH as an innovative strategy for developing functional fruit-based beverages with enhanced nutritional and therapeutic value.